Paraná Seguro Unit (UPS) in Bolsão Audi-União: reflections on the dynamics of urban space - Antunes Brizola, Ana Claudia; Tarcisa Silva Bega, Maria (Seven Editora, 2023)
This article presents some reflections about the production of the urban social space and political decisions based on its representation. It analyzes the political decision of the government of Paraná to install in 2012 the first Paraná Seguro Unit (UPS) in the Audi-União Pocket, located in the Uberaba neighborhood in the city of Curitiba. The UPS are public security policy practices inspired by the Pacifying Police Units of the state of Rio de Janeiro. Starting out, it is hypothesized that the application of the policy was based on the perception of this part of space through the lens of the criminalization of poverty. For the investigation, we analyzed: news about the installation of ups on site, interviews with residents and residents, and these data were articulated with social theories about the production of space. There is in the city of Curitiba, as well as in several others, a peripheral pattern of urban development that leaves several marks in the social production of space and in the conditions of reproduction of life. Therefore, through this study, it was possible to understand that the perception of space from the stigmas and criminalization of poverty led to the development of a public security policy, aiming to produce a space of social control and containment of the poor, drastically modifying the space lived. DOI: https://doi.org/10.56238/tfisdwv1-039